2021
DOI: 10.17718/tojde.906821
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Way of Designing Blended Learning Through Design-Based Research in Higher Education

Abstract: Within higher education, the use of blended learning (BL) is exponentially increased in the 21st century, which poses a number of challenges in designing the process of BL for educators. The aim of this designbased research (DBR) study was to assist an inexperienced educator in teaching and designing a BL course in higher education to convert a face-to-face (F2F) course into a BL course. During the design and delivery of the BL course, what appropriate practices were needed to achieve creating an efficient and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…This encourages self-regulated behaviors such as planning and time management (Broadbent, 2017). Similarly, BL enables the development of reflection and critical thinking and promotes interaction and collaboration between students (Ustun and Tracey, 2021). In addition, studies have reported that the use of BL in higher education is perceived by students to be better when compared to face-to-face or onlineonly learning (Ma and Lee, 2021).…”
Section: Strengths and Challenges For The Implementation Of Blended L...mentioning
confidence: 99%
“…This encourages self-regulated behaviors such as planning and time management (Broadbent, 2017). Similarly, BL enables the development of reflection and critical thinking and promotes interaction and collaboration between students (Ustun and Tracey, 2021). In addition, studies have reported that the use of BL in higher education is perceived by students to be better when compared to face-to-face or onlineonly learning (Ma and Lee, 2021).…”
Section: Strengths and Challenges For The Implementation Of Blended L...mentioning
confidence: 99%
“…Although there were many negative effects of the immediate switch from faceto-face learning to online learning during the pandemic period, it was a desirable positive and optimum situation for students to have low transactional distance perception and high metacognitive awareness. Considering that interaction in distance education plays a very important role in the learning environment such as creating a discussion environment, triggering collaborating learning and ensuring active participation of students (Dumford & Miller, 2018;Ustun & Tracey, 2020;Ustun & Tracey, 2021), the fact that the level of interaction was high according to the results was one of the indicators for a beneficial learning environment in which students took maximum advantage. Besides, the high level of students' metacognitive awareness shows that students were able to successfully learn by choosing the most appropriate strategies for the acquisition of knowledge and skills in distance education, and they were able to make their own self-evaluations at the end of the teaching process.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmada ayrıca üniversite öğrencilerinin pandemi döneminde işlemsel uzaklık algı ve bilişötesi farkındalık düzeylerinin cinsiyete, bölüme, öğretim türüne, yaşadığı bölgeye, bilgisayar sahibi olup olmama durumuna ve internette geçirilen zamana göre anlamlı derecede farklılık gösterip göstermediği incelenmiştir. (Dumford & Miller, 2018;Ustun & Tracey, 2020;Ustun & Tracey, 2021)…”
Section: Yöntemunclassified
“…Jost et al [37] reviewed the role of learners' personalities and behaviors in their academic success in a BL setting. Ustun et al [38] reported a study to assist and teach a BL course in higher education. Bokolo Anthony [6] reported faculty institutional initiatives that affect the implementation of BL.…”
Section: Literature Reviewmentioning
confidence: 99%